O97 Video head impulse test in evaluation of brainstem dysfunction in multiple sclerosis. Issue 9 (September 2017) - Pavicic, Tin; Ruska, Berislav; Pavlovic, Ivan; Skoric, Magdalena Krbot; Crnosija, Luka; Gabelic, Tereza; Adamec, Ivan; Habek, Mario
Abstract : Objectives: The aim of this study was to investigate the role of the video head impulse test (vHIT) in the detection of brainstem lesions in patients with multiple sclerosis (MS). Methods: One hundred thirty participants were enrolled: 66 healthy subjects (HC) (132 ears, 38 females, mean age 45.8 ± 13.7) and 64 MS patients (128 ears, 45 females, mean age 36.8 ± 9.1). The impulses of the head were delivered in 3 planes: lateral, right anterior-left posterior (RALP) and left anterior-right posterior (LARP) with a minimum of 5 head impulses in each plane and direction. vHIT pathology was defined if lateral gain or posterior/anterior slope was lower than 0.7. Results: In HC there was no pathology on lateral and posterior canals, while 16 (12.5%) and 6 (4.7%) out of 128 ears had pathological results on lateral and posterior canals, respectively, in the MS group ( p  < 0.001 and p  = 0.008, respectively). Posterior canal pathology was associated with higher EDSS ( p  = 0.007). Mean gain of the lateral (0.900 ± 0.206 vs. 0.964 ± 0.167, p  = 0.007, respectively) and slope of anterior canals (1.223 ± 0.248 vs. 1.338 ± 0.348, p  = 0.005, respectively) was significantly reduced in MS group compared to HC. MS patients with clinically evident brainstem dysfunction had significantly higher percentage of pathologies of posterior canals p  = 0.017. MS patients with brainstem lesions (specifically midbrain and pontine lesions) had significantly higher percentage of pathologies of posterior canals p  = 0.039 ( p  = 0, 028 and p  = 0.007, respectively). Discussion: Current research has already shown the capability of vHIT to differentiate peripheral causes of vertigo from their central counterparts. However, several publications have shown that central causes of vertigo, especially brainstem stroke can influence vHIT results. Conclusion: Our results indicate that vHIT can detect brainstem dysfunction in patients with MS. Significance: vHIT can be impaired when central part of the vestibular system is damaged.